In Care of the Family. Social welfare in the Polish lands from 19th to 21st century. Historical dictionary [W trosce o rodzinę. Pomoc społeczna na ziemiach polskich od XIX do XXI wieku. Słownik historyczny] as a project carried out under the National Prog - Kinal, Jarosław (Studia Historiae Oeconomicae, 2024)
A team of researchers led by Prof. Dr. Paweł Grata of the University of Rzeszów has received the funding necessary to carry out the project “In Care of the Family: Social assistance in the Polish lands from the 19th to the 21st century. Historical dictionary” under the National Program for the Development of the Humanities. The project will be carried out from 2024 to 2028. The amount of funding amounted to more than one million seven hundred thousand zlotys.